Peran Akhlakul Karimah Dalam Memperkuat P5 Kurikulum Merdeka - Mansyur, Mansyur (Peneliti.net, 2023)
The independent curriculum has broad dimensions. This curriculum addresses various aspects. Pancasila, as the basis of the Indonesian state, has many values that can be taken as a forum for future curriculum development. This study uses a qualitative method. The stages consist of data collection, data reduction, data presentation and conclusions and evaluation. Respondents consisted of teachers, school principals and junior high school students. The results of the research show that the role of akhlakul karimah is an integral part that must be achieved by students. Independent curriculum is one way to develop student behavior.